Orlicz b–metric spaces of infinite matrix and their Köthe –Toeplitz duals. Issue 7 (17th November 2018) - Raj, Kuldip; Pandoh, Suruchi; Devi, Manisha
Abstract: In this paper we introduce and study some spaces of sequences for Orlicz functions and infinite matrices via notion of b – metric. We study the property of completeness of such spaces and derive the interrelationships of these spaces. Finally, we determine their algebraic duals.